Physicochemical Properties, Nutritional and Sensory Quality of “Batuan” [ Garcinia binucao (Blco.) Choisy] Fruits - Quevedo, Elizabeth S.; Laurena, Antonio C.; Merca, Florinia E. (Annals of Tropical Research, 2013)
The physicochemical properties and nutritional profile of the different parts and stages of maturity of “batuan” [Garcinia binucao (Blco.) Choisy] fruits in the Visayas State University (VSU) were determined using standard analytical methods to validate their use as a safe food ingredient. Sensory evaluation on the acceptability of the dry, powdered “batuan” fruits as souring agent in fish stew dish was also conducted. Proximate composition, physicochemical properties and nutrient composition between parts and fruit maturity varied to some level. The pulp which constituted the biggest part of the fruit and the immature ones contained high moisture and acidity that decreased as the fruit matured. Ash, protein, sugar, starch, total carbohydrates, total soluble solids, and sodium content were low in “batuan” fruits. The seeds contained high crude fat, crude protein, and tannin. “Batuan” fruits were also found high in vitamin C, potassium, phosphorus, calcium, magnesium, iron, and trace levels of zinc, copper and manganese. Crude fiber and vitamin A were concentrated in the peel, pulp and ripe fruit. Based on the 9-point Hedonic scale for sensory evaluation, the fresh and the dry, powdered “batuan” fruits were comparable to one another in terms of color, mouth feel, taste and general acceptability as souring agent for fish stew. Results showed that “batuan” fruits have good physicochemical properties and nutrient contents which are comparable or even higher than some conventional fruits used as souring agents. The powdered “batuan” fruit is a potential ready-touse souring agent for domestic consumption, food industry, and other applications.